Impact on rats from acute intratracheal inhalation exposures to WTC dusts. (15th April 2020) - Cohen, Mitchell D.; Prophete, Colette; Horton, Lori; Sisco, Maureen; Park, Sung-Hyun; Lee, Hyun-Wook; Zelikoff, Judith; Chen, Lung-Chi
Abstract: Background: Studies have revealed the increased incidence of health disorders in First Responders (FR) who were at Ground Zero over the initial 72 hr after the World Trade Center (WTC) collapses. Previous studies in rats exposed to WTC dusts using exposure scenarios that mimicked FR mouthbreathing showed exposure led to altered expression of genes whose products could be involved in lung ailments. Nevertheless, it was uncertain if repeated exposures (as occurred in earliest days post-disaster) might have given rise to long-term changes in the lungs/other organs, in white blood cell (WBC) profiles, and/or systemic expression of select (mostly immune-related) proteins. Methods: To examine this, rats were exposed on 2 consecutive days (2 hr/d, intratracheal inhalation) to WTC dusts and then examined over a 1-yr period thereafter. At select times post-exposure, organ (lung, heart, liver, kidney, spleen) weights, WBC profiles, and blood levels of a variety of proteins were evaluated. Results: The study showed that over the 1-yr period, there were nominal effects on organ weights (absolute, index) as a result of the dust exposures. There were significant changes (relative to in naïve rats) in WBC profiles, with exposed rats having increased monocyte-macrophage and decreased lymphocyte percentages. The study also found that dust exposure led to significant systemic increases in many proteins, including MCP-1, RANTES, MMP-9, RAGE, and Galectin-3. Conclusions: These results provide further support for our longstanding hypothesis that the WTC dusts could potentially have acted as direct inducers of many of the health effects that have been seen in the exposed FR.